CYP17 gene polymorphic sequence variation is associated with hyperandrogenism in Kashmiri women with polycystic ovarian syndrome. (4th March 2021) - Ashraf, Sairish; Rasool, Shayaq Ul Abeer; Nabi, Mudasar; Ganie, Mohd Ashraf; Jabeen, Farhat; Rashid, Fouzia; Amin, Shajrul
Abstract: Objective: Polycystic ovarian syndrome is a complex reproductive as well as endocrinological disorder characterized by anovulatory dysfunction, androgen excess and polycystic ovarian morphology. Hyperandrogenism is regarded as a cardinal feature of the disease. It is believed that the excess androgens are produced due to abnormality in steroid biosynthesis pathway wherein cytochrome P450, 17α-hydroxylase (CYP17) plays an imperative role. Therefore the objective of the present study was to analyze the T/C polymorphism in 5'UTR of CYP17 gene for its association with PCOS and hyperandrogenism in Kashmiri population. Method: A total of 700 subjects which included 394 PCOS patients and 306 healthy controls were recruited for the study. Their anthropometric, biochemical and hormonal parameters were analyzed. DNA was extracted followed by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) to analyze the relationship of CYP17 gene polymorphism with PCOS and hyperandrogenism in PCOS. Results and conclusion: The allelic as well as genotypic distribution did not show any significant difference between the cases and controls. However, PCOS patients with mutant genotype had significantly higher level of total testosterone and clinical features like FG score, alopecia than those of wild and heterozygous genotype, indicating association with hyperandrogenism in our Kashmiri population.